2020
DOI: 10.1101/2020.04.23.20077321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Growth Rate Decreases with Social Capital

Abstract: Background Social capital has been associated with many public health variables including mortality, obesity, diabetes, and sexually-transmitted disease rates. However, the relationship of social capital to the spread of infectious disease like COVID-19 is lacking. The COVID-19 pandemic presents an unprecedented threat to global health and economy, for which control strategies have relied on aggressive social distancing. However, an understanding of how social capital is related to changes in human mobility pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…While the concept of social capital has been highly criticized as being "theoretically underdetermined and fuzzy" (Herrmann-Pillath 2010:327; Bjørnskov and Sønderskov 2013;Carpiano 2006), it is nevertheless a useful one because, as Christoforou (2013:720) points out, it highlights "aspects of human agency, particularly individuals' capability to serve wider public benefits of social welfare based on a sense of social obligation and shared identity." Most recently, a growing literature shows that social capital can largely explain the differences in community response and therefore affect the spread of COVID-19 (e.g., Bai, Jin, and Wan 2020;Barrios et al 2020;Bartscher et al 2020;Borgonovi and Andrieu 2020;Ding et al 2020;Fraser and Aldrich 2020;Kuchler, Russel, and Stroebel 2020;Markridis and Wu 2020;Varshney and Socher 2020;. Conclusions from these studies, however, are inconsistent and sometimes contradictory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the concept of social capital has been highly criticized as being "theoretically underdetermined and fuzzy" (Herrmann-Pillath 2010:327; Bjørnskov and Sønderskov 2013;Carpiano 2006), it is nevertheless a useful one because, as Christoforou (2013:720) points out, it highlights "aspects of human agency, particularly individuals' capability to serve wider public benefits of social welfare based on a sense of social obligation and shared identity." Most recently, a growing literature shows that social capital can largely explain the differences in community response and therefore affect the spread of COVID-19 (e.g., Bai, Jin, and Wan 2020;Barrios et al 2020;Bartscher et al 2020;Borgonovi and Andrieu 2020;Ding et al 2020;Fraser and Aldrich 2020;Kuchler, Russel, and Stroebel 2020;Markridis and Wu 2020;Varshney and Socher 2020;. Conclusions from these studies, however, are inconsistent and sometimes contradictory.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson's remark is not without empirical support. In fact, social capital, which captures the features of social organizations and formal and informal norms within societies (Coleman 1990;Putnam 2000), has been shown to powerfully predict the diverse COVID-19 responses (e.g., Bai, Jin, and Wan 2020;Barrios et al 2020;Bartscher et al 2020;Borgonovi and Andrieu 2020;Ding et al 2020;Fraser and Aldrich 2020;Kokubun 2020;Kuchler, Russel, and Stroebel 2020;Makridis and Wu 2020;Miao and Zeng 2020;Varshney and Socher 2020;. In the United States, for example, scholars find that counties or states with more social capital tend to have higher testing rates , less social mobility (Borgonovi and Andrieu 2020), more engagement in social distancing (Ding et al 2020) as well as fewer confirmed cases and slower infection growth rates (Markridis and Wu 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies conducted in the United States lend support to the importance of social capital in the COVID-19 response, with the growth rate of new COVID-19 cases found to be negatively associated with the amount of social capital at both the state and county levels [ 4 ]. However, explicitly seeking to employ or strengthen existing social networks for the purpose of improved health outcomes demands thoughtful consideration as to the nature of each intervention group’s social layout.…”
Section: Social Capital and Covid-19: Challenges And Opportunitiesmentioning
confidence: 99%
“…Moreover, in the United States, a higher social capital was found to be positively correlated with decreased mobility (Borgonovi and Andrieu, 2020), highlighting the reduction of community transmission, better self-sustenance, improved health outcomes, and associated psychosocial impacts. Similar studies suggest that social capital is negatively associated with COVID-19 growth rates and retail/recreational movements, and positively associated with residential movement (Varshney and Socher, 2020). This indicates that communities with high social capital may respond more efficaciously than those with low social capital (Pitas and Ehmer, 2020).…”
Section: Social Capital and Covid-19: Implications For Mental Healthmentioning
confidence: 58%